The European Union and the Global Arena: In Search of Post-Brexit Roles - Michael Smith (Politics and Governance, 2019)
This article explores the issues faced by the EU in developing its international roles post-Brexit, using a combination of discursive analysis and role theory to investigate the development and performance of roles in a number of linked arenas. Central to this analysis is the assumption that whatever form Brexit takes, the EU and the UK will remain closely entangled, and thus that the post-Brexit role assumed by the UK will shape the evolution of EU external action. But a key task for analysis is to place the impact of Brexit into the array of wider forces affecting EU external action, and this is a key aim of the article. The article begins by exploring the discourses of globalism characteristic of UK and EU foreign policies, as focused by the debates about ‘global Britain’ and EU global strategy since 2015. It then introduces a simple framework for considering the roles conceived and performed by the EU, and their potential impact in the post-Brexit world. The article then considers three areas of EU external action, and the ways in which they might be shaped by a post-Brexit world: trade and development, transatlantic relations and security and defence policy. The conclusion discusses the implications of the cases, especially in relation to the conversion of discursive role constructs into performable roles—a problem central to EU external action—and concludes that whilst the impact of Brexit will be significant, it is likely to be less fundamental than the impact of the challenges faced by the EU in the global arena more broadly.